Les cultures fourragères - Klein, Henri-Dominique (éditions Quae, 2014)
Tropical forage crops used to feed the livestock are of crucial important in the sustainable development of hot regions. The first part of this work is intended to guide the choice of forage plants and their crops (diversity of forage plants and their uses based on environments and livestock systems). The second focuses on the growing and management of forage crops (production techniques from planting to harvesting the crops). The challenges of woody forage, production of forage seed and the economics of forage production are also addressed. A CD-ROM presents case studies, illustrations and sheets for each plant.